Ocean acidification effects on stable isotope signatures and trophic interactions of polychaete consumers and organic matter sources at a CO2 shallow vent system - Ricevuto, E; Gambi, MC; VIZZINI, Salvatrice (Journal of Experimental Marine Biology and Ecology, 2015)
Stable carbon and nitrogen isotope analysis (SIA)was used to examine trophic interactions in a naturally acidified shallow coastal CO2 area in the Mediterranean Sea. SIA was helpful to determine the potential effects of ocean acidification (OA) on the interactions of organic matter sources and polychaete consumers, which appear to be tolerant to high pCO2. Mesoherbivore consumers, represented by three polychaete species, Platynereis dumerilii (Audouin and Milne Edwards, 1834) (Nereididae), Polyophthalmus pictus (Dujardin, 1839) (Opheliidae) and Syllis prolifera Krohn, 1852 (Syllidae), are abundant in the low pH conditions of the CO2 vents. Samples of consumers and potential organic matter sources (macroalgae, seagrass and epiphytes)were collected in two periods (May-June and Oct-Nov 2012) in two acidified areas (Castello Aragonese CO2 vents, off Ischia, Italy) and in two control areas. Results suggest a substantial effect of high pCO2 on isotopic composition of both organic matter sources and consumers. The recurring 13C depletion observed in the acidified sites is probably due to an increase in carbon availability and to the exploitation of volcanic-derived dissolved inorganic carbon (DIC) present in the area. The nutritional quality of organic matter sourceswas higher in lowpH stations, where indeed C:N ratios decreased. Despite the occurrence of these effects, the trophic habit of high pCO2 tolerant polychaete consumers seems not to be dramatically affected. Our findings shed the light on how some benthic organisms may respond well to near-future OA conditions, exhibiting high plasticity also in their feeding habits, without being subject to dramatic ecological changes.